Penerapan Six Sigma pada Proses Fabrikasi untuk Menurunkan Biaya Rantai Pasok - Wahyu Poncotoyo; Sesaria Mardhiani Rachma; Sekar Widyastuti Pratiwi (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2019)
Research aims to analyze the application of Six Sigma in order to support the improvement of fabrication process capabilities. The improvement of fabrication process capability is expected to have an impact on the overall reduction in production and logistics costs, which we called a supply chain costs. A case study at a fabrication company was carried out to calculate the capability of the fabrication process and make improvements by applying the Six Sigma method. In this case, product quality that produced from the fabrication process largely determines the supply chain costs incurred by the company. Minitab software is also used in processing and analyzing data. This research shows that improving the fabrication process capability has an impact on reducing product defects so that supply chain costs are lower. Research provides an illustration for the industry that continuous improvement with the aim of reducing the occurrence of product defects will not only have an impact on reducing production costs, but also on logistics costs. As the Six Sigma method implemented, the number of defective products has decreased from 8 pcs per 100 pcs Collar products to 0 pc from 100 pcs Collar products. Fabrication process capability of PT BMT reaches Cpk 5.94 with the sigma value 6 Sigma. The implementation of the Six Sigma method also has a positive impact on overall supply chain costs, with a reduction in supply chain costs of 7.6%. So that PT BMT has a fabrication process that is more effective and efficient.